Transient Intermittent Hypoxia Exposure Disrupts Neonatal Bone Strength - Kim, Gyuyoup; Elnabawi, Omar; Shin, Daehwan; Pae, Eung-Kwon (Frontiers in Pediatrics, 2016)
A brief intermittent hypoxia (IH, ambient O2 levels alternating between room air and 12% O2) for 1h immediately after birth resulted in pancreatic islet dysfunction associated with zinc deficiency as previously reported. We hypothesized that IH exposure modulates zinc homeostasis in bone as well, which leads to increased bone fragility. To test this hypothesis, we used neonatal rats and human osteoblasts. To examine IH-influences on osteoblasts devoid of neural influences, we quantified amounts of alkaline phosphatase and mineralization in IH-treated human osteoblasts. Bones harvested from IH-treated animals showed significantly reduced hardness and elasticity. The IH group also showed discretely decreased levels of alkaline phosphatase and mineralization amounts. The IH group showed a decreased expression of ZIP8 or Zrt and Irt-like protein 8 (a zinc uptake transporter), Runx2 (or Runt-related transcription factor 2, a master protein in bone formation), Collagen-1 (a major protein comprising the extracellular matrix of the bone), osteocalcin, and zinc content. When zinc was eliminated from the media containing human osteoblasts using a zinc chelate, and added later with zinc sulfate, Runx2, ZIP8 and osteocalcin expression decreased first, and recovered with zinc supplementation. Adenovirus-mediated ZIP8 over-expression in osteoblasts increased mineralization significantly as well. We conclude that IH impairs zinc homeostasis in bones and osteoblasts, and that such disturbances decrease bone strength, which can be recovered by zinc supplementation.